A reconsideration of Pseudofortuynia and Tchihatchewia as synonyms of Sisymbrium and Hesperis, respectively (Brassicaceae) - German, Dmitry A.; Al-Shehbaz, Ihsan A. (Phytotaxa, 2018)
Pseudofortuynia leucoclada (Boiss.) Khosravi was initially described and was long treated as a member of Hesperis L. whereas Tchihatchewia isatidea Boiss. has never hitherto been assigned to this genus. Currently these species represent monospecific genera, Pseudofortuynia Hedge and Tchihatchewia Boiss., endemic to restricted areas in Iran and Turkey, respectively. Based on a re-evaluation of morphological characters in light of available molecular data, the merger of Pseudofortuynia with Sisymbrium L. and Tchihatchewia with Hesperis is proposed. Relevant combinations are validated.